Overcoming Barriers to University-Industry Cooperation with a Focus on the Information and Communications Technology Sector – the Czech Experience (Economic and Political Thought, 2012)
The article is a critical, in-depth analysis based on the author’s experience,which shows that apart from money and motivation, cooperation of highereducation and science with industry is necessary for the development ofinnovation processes in every country. In order to achieve this objective,universities must open up to the surrounding and undertake cooperation withindustry. The author calls for the creation of senates or university boards thatwould be composed of an adequate proportion of representatives of industryand public life and could play the role of boards of trustees, which exist inother countries.